The rules’ apliccation of the Moroccan Family Code (Mudawana) regulating about the divorce in Spain: the constitutional filter - Cervilla Garzón, María Dolores (CUADERNOS DE DERECHO TRANSNACIONAL, 2018)
This paper analyzes the rules of the Moroccan Family Code that regulate the dissolution of marriage and its effects, from the point of view of Spanish public order. The purpose is to establish its applicability by the Spanish Courts to meet the demands made in this regard by the Moroccan immigrants residing in our country. This is based on a strict concept of public order and respect for multiculturalism as a factor of integration in European societies. The study is supplemented by a critical examination of the cases law issued in this sense.